2022
DOI: 10.3389/fonc.2022.1011969
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a naturally-occurring canine model for early detection and intervention research in high grade urothelial carcinoma

Abstract: BackgroundEarly detection and intervention research is expected to improve the outcomes for patients with high grade muscle invasive urothelial carcinoma (InvUC). With limited patients in suitable high-risk study cohorts, relevant animal model research is critical. Experimental animal models often fail to adequately represent human cancer. The purpose of this study was to determine the suitability of dogs with high breed-associated risk for naturally-occurring InvUC to serve as relevant models for early detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…5,49 Moreover, recent studies using genomic analyses have reported similarities of molecular features between invasive UC in humans and dogs. [50][51][52] With regard to HER2, protein overexpression has been reported in 9.2%-61.1% of human patients with MIUC. [53][54][55][56][57] Both in vitro and in vivo experiments with human UC cell lines have shown an antitumour effect of T-DM1, and the effect has been much stronger than that of trastuzumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,49 Moreover, recent studies using genomic analyses have reported similarities of molecular features between invasive UC in humans and dogs. [50][51][52] With regard to HER2, protein overexpression has been reported in 9.2%-61.1% of human patients with MIUC. [53][54][55][56][57] Both in vitro and in vivo experiments with human UC cell lines have shown an antitumour effect of T-DM1, and the effect has been much stronger than that of trastuzumab.…”
Section: Discussionmentioning
confidence: 99%
“…Human MIUC and canine invasive UC are similar in pathology, biological behaviour, and response to chemotherapy 5,49 . Moreover, recent studies using genomic analyses have reported similarities of molecular features between invasive UC in humans and dogs 50–52 . With regard to HER2, protein overexpression has been reported in 9.2%–61.1% of human patients with MIUC 53–57 .…”
Section: Discussionmentioning
confidence: 99%
“…9 Early detection (whether in the preclinical period or at an earlier stage of disease) has been extensively documented to improve outcomes for many cancer types in humans 26 as well as in dogs. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] A significant concern with all types of cancer screening is the potential for a large number of false positive results, which could lead to unnecessary procedures and expense as well as emotional distress. 5 The high PPV prospectively observed in this study provides reassurance that most OncoK9® CSD results in a high-risk cancer screening population are in fact true positives, and cancer will be found if an adequate confirmatory evaluation is performed.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive urinary carcinoma (iUC) is the most common cancer of the urinary bladder in dogs, accounting for 90% of bladder cancers, with 40,000 newly diagnosed cases a year 12 , 13 . Naturally occurring canine iUC closely mimics human high grade MIBC in terms of age of onset, pathology, cellular and molecular features, metastatic profiles, and treatment response 14 . Approximately 50% of affected dogs will experience metastases to distant organs 15 and median survival times are typically < one year, although dogs receiving multiple sequential protocols may live beyond a year 16 , 17 .…”
Section: Introductionmentioning
confidence: 90%